2022
DOI: 10.1002/epi4.12649
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of perampanel as the only add‐on: Retrospective, multicenter, observational real‐life study on epilepsy patients

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 20 publications
2
8
0
Order By: Relevance
“…Retention, responder and seizure freedom rates were similar between subgroups with the exception of the ≥50% responder rate (66 vs. 53%; p = 0.05) and the seizure freedom rate (42 vs. 25%; p = 0.005) at 3 months, both significantly higher in the early vs. late add-on subgroup ( 52 ). The most frequently reported AEs were dizziness/vertigo and behavioral changes at all timepoints ( 52 ). Finally, a single-center, open-label study compared the efficacy of PER in individuals with a diagnosis of mesial temporal lobe epilepsy when used as first add-on therapy (due to inefficacy of a first ASM; n = 20) vs. late add-on therapy (due to inefficacy of ≥2 ASMs; n = 17) ( 53 ).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Retention, responder and seizure freedom rates were similar between subgroups with the exception of the ≥50% responder rate (66 vs. 53%; p = 0.05) and the seizure freedom rate (42 vs. 25%; p = 0.005) at 3 months, both significantly higher in the early vs. late add-on subgroup ( 52 ). The most frequently reported AEs were dizziness/vertigo and behavioral changes at all timepoints ( 52 ). Finally, a single-center, open-label study compared the efficacy of PER in individuals with a diagnosis of mesial temporal lobe epilepsy when used as first add-on therapy (due to inefficacy of a first ASM; n = 20) vs. late add-on therapy (due to inefficacy of ≥2 ASMs; n = 17) ( 53 ).…”
Section: Discussionmentioning
confidence: 85%
“…In both FAME and COM-PER, PER was shown to be particularly effective in PWE with FBTCS ( 49 , 51 ). In the clinical practice setting, a retrospective, observational, multicentre, longitudinal study assessed the effectiveness and tolerability of PER at 3, 6 and 12 months when used as the only add-on to ASM monotherapy in PWE with focal and generalized epilepsy aged >12 years ( 52 ) and a subanalysis was conducted to compare the use of PER as an early single add-on (after 0 or 1 previous add-on therapies) or late single add-on (after ≥2 previous add-on therapies) ( 52 ). Retention, responder and seizure freedom rates were similar between subgroups with the exception of the ≥50% responder rate (66 vs. 53%; p = 0.05) and the seizure freedom rate (42 vs. 25%; p = 0.005) at 3 months, both significantly higher in the early vs. late add-on subgroup ( 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…26 The final study was an Italian, multicenter, observational, retrospective study, in which PER was shown to be effective and well tolerated as only add-on therapy in 503 PWE with focal, generalized, or undetermined epilepsy treated for up to 12 months, although outcomes were not reported separately for PWE with generalized epilepsy. 27 No ASM has class I or II evidence of efficacy as initial monotherapy in people with IGE, 33 and treatment options are currently limited. Certain ASMs-particularly sodium channel blockers, such as carbamazepine, phenytoin, and in some instances also lamotrigine-can worsen seizure control in IGE and/or precipitate absence or myoclonic status epilepticus.…”
Section: F I G U R Ementioning
confidence: 99%
“…17,18 Clinical practice studies provide evidence on how a drug performs when used outside the relative restrictions of clinical trials, [19][20][21] but real-world evidence on the use of PER to specifically treat IGE is currently limited. [22][23][24][25][26][27] The PERaMpanel pooled analysIs of effecTiveness and tolerability (PERMIT) study included approximately 5200 people with focal and generalized epilepsy who were treated with PER in clinical practice. 28 The purpose of this study was to assess the real-world effectiveness and safety/ tolerability of PER when used to treat people with IGE included in PERMIT.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation